Scalp defect associated with extensive fibrosis of artificial dura requiring modified closure (Bangladesh Journal of Medical Science, 2024)
Background A variety of methods are available for scalp defect closure and necessitate extensive planning. Superficial temporal artery (STA) based local flaps are widely used in the field of scalp and face reconstruction because of their flexibility and rich vascularity. Rotation and transposition techniques are commonly used in the area, however at times result in excessive tension. V-Y advancement allows tension-free closure with reduced post-operative complications. Case presentation A case of scalp defect post multiple craniectomies for a traumatic head injury complicated with subgaleal collection and poor wound healing in a 29-year-old male, is reported. Due to the nature of defect, with underlying fibrosis and previous artificial duraplasty, along with location in the frontotemporal region, a local STA based flap closed in a rotation, transposition and unilateral V-Y advancement pattern was used. Conclusion The challenges encountered in wound closure of complicated post-traumatic and multiple craniectomy cases can be overcome with a modified combined approach which achieves optimal wound closure.Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1227-1232